Sigma phase precipitation on welded SAF 2205 Duplex Stainless Steels after isothermal heat treatment. Issue 1611 (2014) - Pérez, A. F. Miranda; Sandström, R.; Calliari, I.; Valdés, F. A. Reyes
ABSTRACT: Duplex stainless steels are commonly used for various applications owing to their superior corrosion resistance and/or strength. They have ferromagnetic behavior together with a good thermal conductivity and a lower thermal expansion as a result of higher ferrite content than austenitic steels. Their ferrite matrix suffers a decomposition process during aging in the temperature range 650-950° C producing precipitation of austenite, σ and χ, carbides and nitrides. These intermetallic phases are known to be deleterious for corrosion resistance and mechanical properties. In this work the effect of aging time during isothermal treatment at 850°C and 900°C on the microstructure of SAF 2205 Duplex Stainless Steels welded plates has been investigated. The aim of this work is to determine the morphology of σ phase, and perform a quantitative analysis of the precipitation process. Submerged Arc Welding is used for processing. It produces a high content of δ ferrite in the heat affected zone and low content of austenite in the weld. Microstructural examination shows that the σ phase precipitates at δ ferrite/γ interphases. Longer aging treatments give rise to an increase of volume fraction together with a coarser morphology.